2016
DOI: 10.21037/jtd.2016.04.65
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment outcomes between single-port video-assisted thoracoscopic anatomic segmentectomy and lobectomy for non-small cell lung cancer of early-stage: a retrospective observational study

Abstract: Background: There are few reports of single-port video-assisted thoracoscopic surgery (S-VATS) anatomic segmentectomy and S-VATS lobectomy for early-stage non-small cell lung cancer (NSCLC) and no comparisons between them have yet been reported. Therefore, the aim of this study was to compare the safety and efficacy of S-VATS anatomic segmentectomy and S-VATS lobectomy for early-stage NSCLC.Methods: In this retrospective observational study, the outcomes of 79 consecutive patients who had undergone S-VATS anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
(18 reference statements)
0
7
2
Order By: Relevance
“…Neither the dissection of the intersegmental plane nor the parenchymal compression during segmentectomy seem to increase the risk of pulmonary complications. A few retrospective studies compared postoperative complication rate after VATS anatomical resections and found contradictory results [9–13]. Our finding of no difference between segmentectomy and lobectomy in incidence of cardiopulmonary complications contrasts with the findings of Deng et al [9] This study shown a higher incidence of PAL and pulmonary complications after VATS segmentectomy.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Neither the dissection of the intersegmental plane nor the parenchymal compression during segmentectomy seem to increase the risk of pulmonary complications. A few retrospective studies compared postoperative complication rate after VATS anatomical resections and found contradictory results [9–13]. Our finding of no difference between segmentectomy and lobectomy in incidence of cardiopulmonary complications contrasts with the findings of Deng et al [9] This study shown a higher incidence of PAL and pulmonary complications after VATS segmentectomy.…”
Section: Discussioncontrasting
confidence: 91%
“…Recently, Song et al reported similar rates of postoperative pulmonary complications (15.3%) between segmentectomy ( N = 41) and lobectomy ( N = 122) [10]. Finally, Lin et al compared segmentectomy ( N = 32) and lobectomy ( N = 47) by a single-port approach, finding no difference in the postoperative complication rate ( P = 0.19) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncological adequacy is a major concern in cancer surgery. The prognosis of patients who undergo lobectomies versus segmentectomies for primary lung cancer less than 2 cm has been shown to be similar [12][13][14] and that of complex versus simple segmentectomies was also comparable. 3,15) For UP-VATS, we yielded similar stations and numbers of mediastinal LNs as for when we performed MP-VATS.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with wedge resection, segmentectomy is preferred because of its sufficient surgical margin, its evaluation of lymph nodes, and its superiority oncological outcomes (14,15). As a lung-sparing procedure, segmentectomy was shown to achieve equal short-term surgical results and long-term oncological outcomes compared with lobectomy (16,17). However, most of these studies were retrospective, and some results are contradictory (18) There are 2 on-going prospective randomized controlled clinical trials regarding segmentectomy, whose long-term outcome data are not yet available (19,20).…”
Section: Discussionmentioning
confidence: 99%